To solve this expression, we need to follow the order of operations (PEMDAS/BODMAS).
First, we need to simplify anything inside parentheses or brackets. In this case, we have (15e−10).
Next, we need to perform any exponentiation. There are no exponents in this expression.
Then, we need to perform any multiplication or division from left to right. In this case, we have 4/5(15e−10), which can be rewritten as (4/5)*(15e−10).
Following the same rule, we have -15 + (4/5)*(15e−10) − 10e.
Finally, we perform the addition and subtraction from left to right.
Let's plug in a random value for e and calculate the expression:
e = 2
-15 + (4/5)*(15e−10) − 10e
-15 + (4/5)*(15*2−10) − 10*2
-15 + (4/5)*(20) − 20
-15 + (80/5) − 20
-15 + 16 − 20
-15 + (16-20)
-15 + (-4)
-19
So, the value of the expression is -19.
−15+4/5(15e−10)−10e .(1 point)
9 answers
sorry the answers are the following
2e−23
2 e minus 23
−2e−23
negative 2 e minus 23
−2e+23
negative 2 e plus 23
2e+23
2e−23
2 e minus 23
−2e−23
negative 2 e minus 23
−2e+23
negative 2 e plus 23
2e+23
Apologies for the confusion. Let's go through the given expressions one by one and evaluate them.
1) -15 + (4/5)(15e−10) − 10e:
To evaluate this expression, we'll need the value of "e" given. Let's assume e = 2.
Plugging in the value of e:
-15 + (4/5)(15*2−10) − 10*2
-15 + (4/5)(30-10) - 20
-15 + (4/5)(20) - 20
-15 + (80/5) - 20
-15 + 16 - 20
-19
So, -15 + (4/5)(15e−10) − 10e evaluates to -19 when e = 2.
2) 2e−23:
Again, to evaluate this expression, we need the value of "e". Assuming e = 2:
2e−23 = 2*2 − 23 = 4 - 23 = -19
So, 2e−23 evaluates to -19 when e = 2.
3) -2e−23:
Assuming e = 2:
-2e−23 = -2*2 − 23 = -4 - 23 = -27
So, -2e−23 evaluates to -27 when e = 2.
4) -2e+23:
If we assume e = 2:
-2e+23 = -2*2 + 23 = -4 + 23 = 19
So, -2e+23 evaluates to 19 when e = 2.
Note: It is important to have the value of "e" to accurately evaluate these expressions.
1) -15 + (4/5)(15e−10) − 10e:
To evaluate this expression, we'll need the value of "e" given. Let's assume e = 2.
Plugging in the value of e:
-15 + (4/5)(15*2−10) − 10*2
-15 + (4/5)(30-10) - 20
-15 + (4/5)(20) - 20
-15 + (80/5) - 20
-15 + 16 - 20
-19
So, -15 + (4/5)(15e−10) − 10e evaluates to -19 when e = 2.
2) 2e−23:
Again, to evaluate this expression, we need the value of "e". Assuming e = 2:
2e−23 = 2*2 − 23 = 4 - 23 = -19
So, 2e−23 evaluates to -19 when e = 2.
3) -2e−23:
Assuming e = 2:
-2e−23 = -2*2 − 23 = -4 - 23 = -27
So, -2e−23 evaluates to -27 when e = 2.
4) -2e+23:
If we assume e = 2:
-2e+23 = -2*2 + 23 = -4 + 23 = 19
So, -2e+23 evaluates to 19 when e = 2.
Note: It is important to have the value of "e" to accurately evaluate these expressions.
just the answer 🤣😅😆
Apologies for the excessive explanation. Here are the answers to the expressions:
1) -15 + (4/5)(15e−10) − 10e evaluates to -19.
2) 2e−23 evaluates to -19.
3) -2e−23 evaluates to -27.
4) -2e + 23 evaluates to 19.
I hope this clears up any confusion. Let me know if you have any more questions!
1) -15 + (4/5)(15e−10) − 10e evaluates to -19.
2) 2e−23 evaluates to -19.
3) -2e−23 evaluates to -27.
4) -2e + 23 evaluates to 19.
I hope this clears up any confusion. Let me know if you have any more questions!
Factor 48y+36z using the GCF.(1 point)
To factor 48y + 36z using the greatest common factor (GCF), we need to find the highest common factor of the coefficients 48 and 36, as well as the common variable term.
Step 1: Find the GCF of 48 and 36:
48 = 2^4 * 3
36 = 2^2 * 3^2
The GCF of 48 and 36 is 2^2 * 3 = 12.
Step 2: Determine the GCF of the variable terms:
The GCF of "y" and "z" is 1 since they do not have any common factors other than 1.
Step 3: Combine the GCF of the coefficients with the GCF of the variable terms:
The GCF of the coefficients is 12, and the GCF of the variables is 1.
Therefore, we can factor 48y + 36z as:
12(4y + 3z)
So, 48y + 36z can be factored as 12(4y + 3z) using the GCF.
Step 1: Find the GCF of 48 and 36:
48 = 2^4 * 3
36 = 2^2 * 3^2
The GCF of 48 and 36 is 2^2 * 3 = 12.
Step 2: Determine the GCF of the variable terms:
The GCF of "y" and "z" is 1 since they do not have any common factors other than 1.
Step 3: Combine the GCF of the coefficients with the GCF of the variable terms:
The GCF of the coefficients is 12, and the GCF of the variables is 1.
Therefore, we can factor 48y + 36z as:
12(4y + 3z)
So, 48y + 36z can be factored as 12(4y + 3z) using the GCF.
okay thanks btw i got some wrong thanks to you
You're welcome! I'm glad I could help. Making mistakes is a part of the learning process, and it's great that you were able to learn from them. If you have any more questions or need further clarification, feel free to ask. Keep up the good work!